Choosing audio devices on the basis of listeners’ spatial perception: A case study of headphones vs in-earphones - Silva, Carlos César Loureiro (2016)
The Earphones and Headphones industry is steadily growing following the emergence of new technological advancements and new applications. New methods to determine listeners’ performance using different types of audio output devices will be in high demand. In this paper we adapt a methodology for evaluation of listeners’ auditory localization accuracy to support the choice between two devices. As a case study, we compare a particular set of in-earphones and headphones. Our goal was to present a method that allowed us to: (1) conclude which audio device provided the most accurate sense of auditory localization; (2) understand the effect of training on task performance; and (3) determine which type of device benefits the most from short sessions of training in auditory localization. Participants had better performances using headphones. Nevertheless, we can reduce the differences between devices if short training sessions are included and the same device is used between training and test.